FÉMINICIDE: INSTITUTIONAL SILENCE ON THE SCREAMS OF MURDERED WOMEN IN FRANCE - Syarif, M. Afif Alfadin; Miranda, Airin (Paradigma: Jurnal Kajian Budaya, 2026)
Rising awareness of women's homicide in France has challenged the government to provide an adequate legal response, as feminist groups began advocating and expressing the discourse on women's homicide since 2014 through the term féminicide. The nature of this crime remains contentious in legal discourse, particularly given the significant rise in féminicide cases in 2019. This study, therefore, aims to examine the phenomenon of féminicide in France, exploring both the discourse surrounding it and the legal responses from the government. Drawing on 46 cases recorded in 2023 by the feminist collective #NousToutes, and with particular attention to relevant legal provisions and feminist advocacy, this research adopts a qualitative approach framed within Bartlett's feminist legal methods (1990) and Foucault’s concept of power (1976). The study argues that the French government has effectively excluded and alienated féminicide from the continuum of violence against women through Article 171 of law n° 2017-86 of 27 January 2017, which generalizes experiences of gender-based violence, aligning with the indifference and neglect of legal authorities that exacerbate violence against women. Consequently, the féminicide remains acute and trivialized.